2020
DOI: 10.1111/php.13269
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Effects of 222‐nm ultraviolet radiation C Sterilizing Lamps on Mice Susceptible to Ultraviolet Radiation

Abstract: Germicidal lamps that emit primarily 254 nm ultraviolet radiation (UV) are routinely utilized for surface sterilization but cannot be used for human skin because they cause genotoxicity. As an alternative, 222‐nm UVC has been reported to exert sterilizing ability comparable to that of 254‐nm UVC without producing cyclobutane pyrimidine dimers (CPDs), the major DNA lesions caused by UV. However, there has been no clear evidence for safety in chronic exposure to skin, particularly with respect to carcinogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
129
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(151 citation statements)
references
References 39 publications
9
129
1
6
Order By: Relevance
“…An exposure dose as low as 1.2 to 1.7 mJ/cm 2 of 222-nm light inactivates 99.9% of the airborne human coronavirus tested from both subgroups beta and alpha, respectively. Together with previous safety studies [12][13][14][15][16][17][18] and our earlier studies with aerosolized influenza A (H1N1) 23 , these results indicate that far-UVC light is a potentially powerful and practical approach for reduction of airborne viral transmission, without the human health hazards associated with conventional germicidal UVC lamps. Benchtop Aerosol Irradiation Chamber.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…An exposure dose as low as 1.2 to 1.7 mJ/cm 2 of 222-nm light inactivates 99.9% of the airborne human coronavirus tested from both subgroups beta and alpha, respectively. Together with previous safety studies [12][13][14][15][16][17][18] and our earlier studies with aerosolized influenza A (H1N1) 23 , these results indicate that far-UVC light is a potentially powerful and practical approach for reduction of airborne viral transmission, without the human health hazards associated with conventional germicidal UVC lamps. Benchtop Aerosol Irradiation Chamber.…”
Section: Discussionsupporting
confidence: 78%
“…The sensitivity of the coronaviruses to far-UVC light, together with extensive safety data even at much higher far-UVC exposures [12][13][14][15][16][17][18] , suggests that it will be feasible and safe to have the lamps providing continuous far-UVC exposure in public places to significantly reduce the probability of of 2 would halve these disinfection times, while still maintaining safety [12][13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, recent studies have shown that 222-nm UVC is less harmful than 254-nm UVC because far-UVC light has a very limited penetration depth in the skin or eyes and it is also an efficient anti-microbial technology. [9][10][11][12][13] Therefore, a 222-nm UVC disinfection system could be used in occupied public spaces including a hospital room, which is occupied by patients and frequented by health care workers and possibly, visitors. However, further study about the safety and efficacy of 222-nm UVC irradiation in occupied space is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that 222-nm UVC light, belonging to far-UVC (207-222 nm), has the same highly effective germicidal properties as 254-nm UVC; however, it is less harmful to the skin and eyes than 254-nm UVC because far-UVC light has a very limited penetration depth in the skin or eye. [9][10][11][12][13] In addition, previous studies have reported that low dose of 222-nm UVC inactivated aerosolized H1N1 influenza virus and human coronaviruses alpha HCoV-229E and beta HCoV-OC43. 14,15 Although there are a few reports about the effectiveness of UV disinfection on SARS-CoV-2, 16,17 the effect of 222-nm UVC on SARS-CoV-2 is poorly understood.…”
mentioning
confidence: 99%